Bridging Communities. A community centre to encourage and facilitate intergenerational connections in Johannesburg - Lachman, Kaylene (University of the Witwatersrand, Johannesburg, 2024)
The aim of this project is to create a safe space to facilitate and encourage intergenerational connections between the elderly and children whilst revitalising an underused park. The safe space will be a community centre that acts as a social hub where children and the elderly are able to work cohesively alongside each other, allowing for more meaningful interactions and mutual learning between the generations. The connections created through these interactions can foster more trust and empathy in the community. These shared spaces will allow the opportunity for the different generations to mutually benefit from each other. Some of these benefits include skill development, cultural preservation, mentorship programs and the improvement of mental and physical wellbeing of both generations. The intergenerational connections formed in this community centre can combat social isolation amongst the elderly. It can provide an enlightening and educational experience for the children. The revitalisation of the neglected urban space will create an enriching experience for the community as bridging the generational gaps will create deeper community bonds and improve the quality of life for all within the community.
A research report submitted in fulfillment of the requirements for the Master of Architecture, In the Faculty of Engineering and the Built Environment , School of Architecture and Planning, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Intergenerational connections; community centre; SDG-11: Sustainable cities and communities